ICPSR Data Holdings 1996
DOI: 10.3886/icpsr06744.v2
|View full text |Cite
|
Sign up to set email alerts
|

Dutch Parliamentary Election Studies Data Source Book, 1971-1989

Abstract: The main purpose of this data collection was to provide directly accessible information on change and stability of electoral behavior and political orientation in the Netherlands. This dataset is a compilation of common core variables included in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…56 Nevertheless, studies using validated voting data repeatedly conclude that, even though they overestimate actual turnout, self-reported survey measures do not lead to biased conclusions about the determinants of voting. Like most survey-based analyses, our study necessarily uses self-reported data.…”
Section: R O B U S T N E S S O F R E S U L T Smentioning
confidence: 99%
“…56 Nevertheless, studies using validated voting data repeatedly conclude that, even though they overestimate actual turnout, self-reported survey measures do not lead to biased conclusions about the determinants of voting. Like most survey-based analyses, our study necessarily uses self-reported data.…”
Section: R O B U S T N E S S O F R E S U L T Smentioning
confidence: 99%